PERSPECTIVES OF INSURANCE MEDICINE IMPLEMENTATION IN UKRAINE - FILIPOVA, NATALIA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
This article is devoted to the implementation of insurance medicine in Ukraine. The market of voluntary medical insurance is considered, the purpose of which is to provide the insured with a guarantee of full or partial reimbursement by the insurer of the costs associated with applying to a medical institution for the service. The conceptual scheme of the impact of health insurance is presented. Medical insurance is developing as a separate area of sale of insurance services aimed at organizing the provision of medical services to insured persons. It is noted that compulsory health insurance is more effective in the formation of financial support for the effective functioning of health care. The development of voluntary health insurance will allow insured persons to independently manage their health care, independently and receive the necessary list of medical services in accordance with their needs, regardless of state support and the current system of social protection. For insurers, the promotion of voluntary health insurance will create additional opportunities to increase insurance premiums and, consequently, income reserves. The results of the SWOT analysis create a detailed picture of the peculiarities of the development of voluntary health insurance and provide an opportunity to identify points of further growth of the insurance market. Continuous modernization, work to improve the effectiveness of insurance medicine through innovation will help to establish effective practices in financing health care and addressing the problems of resource provision of access to high quality medical services and qualified and timely medical care. Prospects for the development of insurance medicine are due to the following defining characteristics of the external environment, which are important to consider when making management decisions, in particular: interdependence and synergy of environmental factors; nonlinearity and uncertainty of the external environment; mobility and chaos of some elements of the environment.
Keywords: health insurance; health care; implementation